STUDY ON MANAGEMENT METHODS OF THE MASSAGE WASTE - Ramona Violeta CAZALBAȘU (Fiabilitate şi Durabilitate)
Waste management is one of the major issues facing Romania in terms of environmental protection. This concerns the collection, transport, treatment, recovery and disposal of waste. Responsibility for waste management activities lies with their generators, according to the "polluter pays" principle or, as the case may be, with producers in accordance with the "producer responsibility" principle. The activities of waste management must be carried out in compliance with environmental protection standards that reflect the requirements of European legislation. European Directives transposed into Romanian legislation have led to a new approach to the waste problem, paying attention to the need to protect and save natural resources, reduce management costs and find effective solutions to reduce pollution.